Comparative Efficacy of Basal-Bolus Versus Premixed Insulin Regimens in Achieving Glycemic Control Among Patients with Type 2 Diabetes Mellitus: A Systemic Review - Khan, Dawood; Zafar, Lintha; Faryal , Sadaf; DurreBeda; Shakeel, Zainab; Muhammad Waqas; Naqeeb Ullah; Nazir, Mahwash; Nazir, Sumaira (Indus Journal of Bioscience Research, 2024)
Background: T2DM is one of the most prevalent chronic illnesses, requiring effective management to prevent complications. Oral antidiabetic agents are typically needed only in the initial stage to control blood glucose level, while insulin therapy becomes essential as the disease progresses. This includes both basal-bolus and premixed insulin regiments. Therefore, defining an optimal treatment schedule is crucial to improve outcomes in T2DM management and minimize associated attack. Objective: This systematic review assesses the efficacy and safety of the basal-bolus regimen compared to premixed insulin in treating glycemia in T2DM. Methods: The study search involved PubMed, EMBASE, Cochrane Library, and Scopus; the search done strictly applied the PRISMA guidelines. A Review of RCTs, cohort studies, and systematic reviews for comparing basal-bolus regimens to the premixed insulin regimens in A-T2DM was done. These were HbA1c, FPG, and PPG. Secondary endpoints were the incidence of hypoglycemia, adherence to therapy, and disease-specific quality of life. Results: From the above search, we identified 45 studies that meet the inclusion criteria. Daily basal-bolus regimens demonstrated a slightly better reduction in HbA1c, FPG, and PPG than premixed regimens with the trade-offs related to hypoglycemia and regimen complexity. However, basal-bolus regimens are disadvantaged by having more hypoglycemia episodes than the a priori premixed regimens for patients requiring fewer injections. Conclusion: While basal-bolus regimens give better glycaemic control than premixed ones, the latter are safer and easier to use in some patients. Sources call into question of patient’s characteristics in particular, features of T2DM, the patient’s behavior, and his/her genetic background in order to come up with the most effective and individualized treatment plan more consequently than in any other case.